Peptide-Loaded Nanoparticles: A Precision Approach to Breast Cancer Treatment - Eltaib, Lina; Alanazi, Mashael N.; Maqbool, Mudasir; Rana, Amita Joshi; Khan, Yumna; Hussain, Md Sadique (Current Drug Delivery, 2025)
Breast cancer (BC) continues to be the most prevalent cause of death from cancer on a global scale, requiring novel and targeted therapeutic strategies. Peptide-loaded nanoparticles (NPs) have been established as a prospective platform for precision drug delivery in BC treatment, providing enhanced cancer selectivity, improved drug stability, and reduced systemic toxicity. This article explores the multifaceted utilizations of peptide-loaded NPs in BC therapeutics, highlighting advancements in targeted drug delivery, combination therapy, and vaccine development. Peptide-loaded NPs have demonstrated superior efficacy in delivering chemotherapeutic agents, overcoming drug resistance, and minimizing adverse effects. Studies on tumor-homing peptides, such as F3-functionalized liquid crystalline NPs and tLyP-1-modified reconstituted high-density lipoprotein NPs, have shown significant improvements in drug accumulation at tumor sites, reduction in metastasis, and prolonged circulation time. Additionally, the creation of peptide-based vaccines targeting tumor-associated antigens, including HER2/neu and heat shock protein 90 (HSP90), is reshaping BC immunotherapy, stimulating strong immune responses against tumors. Despite these advancements, obstacles persist in ensuring NP stability, mitigating immunogenicity, and scaling up manufacturing for clinical translation. Future directions include the integration of peptide-loaded NPs with CRISPR/Cas9 for gene-editing applications, the development of peptide nanovaccines, and the use of personalized nanomedicine approaches tailored to the molecular profiles of individual tumors. This review underscores the potential of peptide-loaded NPs as a next-generation therapeutic strategy, facilitating the development of more efficient and personalized treatments for BC.
Keywords: peptide-based vaccines